Ecos de orixá no palco-terreiro de Maria Bethânia: espaço, performance e cultura afro-brasileira - Silva Júnior, Isley Borges da (2022)
Maria Bethania´s stage, a public space to experience her art, echoes the Yoruba African tradition and its dense philosophical-cultural framework centered on divinized ancestors, called orixas. This PhD Thesis establishes a relationship between the performance of the interpreter Maria Bethania and the Afro-Brazilian sacred spatiality. In this research study, we immerse ourselves in the ancestral and oral traditions of terreiros as a source of knowledge and artistry of this Brazilian interpreter, epithet that we give to the interpreter based on the conclusions we reached with the development of the research. Her body, voice, presence, songs, stage settings, costumes, album liner notes, sustain a performance that brings the discourse on Afro-Brazilian culture to the center of the stage. The theoretical framework comprises studies on the spatiality of the sacred Afro-Brazilian (MENDES, 2015; PORTUGUEZ, 2015; PRANDI, 2001; OLIVEIRA, 1997), formulations on the concept of performance (ZUMTHOR, 2014; COHEN, 2002; OLIVEIRA, 2016), and the critical fortune of the Brazilian song and the singer's trajectory (MARCOS, 2008). The methodology employed is autoethnography (SANTOS, 2017), which reflects the author´s path as regards experience in candomble ketu and knowledge of African tradition through orality in the terreiro. The results indicate a unique performance that mobilizes ancestral knowledge from within Brazilian terreiros, evoking the spiritualities of the land, waters, forests, and winds.